Computation of Modal Properties of Two Types of Freight Wagon Bogie Frames Using the Finite Element Method - Dizo, Jan; Harusinec, Jozef; Blatnicky, Miroslav (Manufacturing Technology Journal, 2018)
The aim of this article is to calculate and compare the modal properties of the frame of the standard and modified freight wagon bogie design. Analysed frames represent the main support parts of the bogie, which are most often used in the Central Europe region. Determination of the modal properties belongs to the fundamental but very important step in the engineering design. In our case, modal analyses of bogie frames structures were carried out using the Finite Element Method. In order to perform numerical calculations based on FEM approach, Ansys package was used. Modal analyses of individual parts as well as substructures of rail vehicles is an inseparable part of the rail vehicles design process. In this article theoretical and practical consequences of obtained results from the modal analysis, i.e. eigenmodes and eigenfrequences of the analysed part of the bogie on its dynamic properties are presented.
Keywords: Freight wagon bogie; Finite element method; Modal analysis; Modified design